Studying the Factors effect on Separation of Two Solid Equivalent Particle According to Density and Determination the best Separation Point - Salih, Suha (Anbar Journal of Engineering Sciences, 2022)
Density separation has many applications in metallurgy, medicine, clinical chemistry, microbiology, and agriculture. This study investigates the factors’ effects on density separation in order to benefit from this technique. The separation quality depends on the velocity of particles because as the velocity of particles increases, the mean separation needs less time so it gives better separation, so the parameter effect on the value of the velocity is studied. These parameters were volume fractions, the diameter of the sphere, the density of the sphere, and the viscosity of the fluid. Each parameter was studied by calculating the velocity of particles using Stokes’ law. The velocity of particles is directly proportional to some properties of particles. These properties are the diameter and density of a particle because as these properties increase, the mass of particles increases, which leads to increased kinetic energy, which increases turbulence. Turblance’s velocity is increasing. The volume fraction of spheres is another property of particles’ effects on density separation. This parameter is inversely proportional to velocity because a collision between particles increases, which decreases turbulence. Fluid properties also have an impact on density separation. This property is viscosity. Its effect deteriorates the efficiency of separation because viscosity is the resistance of the fluid to flow that serves to displace the particle, which leads to a reduction in the velocity of the particle. The maximum separation happens when the sink and float particles separate at the same time. That happens when the sink and float particles have the same velocity in the opposite direction. That means when the sum of velocities equals zero. In this research, the maximum separation was derived when the sum of velocities equaled zero.